Proses Evaluasi Kinerja Guru Di SMP Negeri 47 Surabaya - Bahriatul Ilmi; Ummi Latifah; Hanivia Cindy, Agustin; Windasari, Windasari (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2024)
Teacher performance is a description of how teachers act, the skills, values ​​and knowledge that teachers have in carrying out their responsibilities and functions. The purpose of this writing is to find out how the process of evaluating teacher performance at SMP Negeri 47 Surabaya is, how it is implemented and what guidelines are used in assessing the results of the work of teachers at SMP Negeri 47 Surabaya. The method used in this research is a descriptive qualitative method, with data collection methods in the form of observation, interviews and literature study. The result is that SMP Negeri 47 Surabaya in the process of evaluating teacher performance uses the results of teacher supervision and observation as the implementation. The stages in this process begin with an analysis of the learning focus that needs to be improved, followed by the creation of a RPP (learning implementation plan) by the teacher and uploading the RPP in the PMM (independent teaching program) application, and continued with the observation process according to the behavioral targets uploaded by the teacher , after that the process of measuring the achievement of the RPP, and ending with evaluation and reflection.